2017
DOI: 10.21608/jpp.2017.41138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sowing Dates, Irrigation Intervals and Organic Fertilizers on Growth and Productivity of Pea Plants (Pisum sativum L.) under Sandy Soil Conditions

Abstract: Two field experiments were conducted during winter seasons of 2014-15 and 2015-16 at the Agric. Res. Station, Veg. Res. Dept., Hort. Res. Inst., Agric. Res. Center, in El-Arish, North Sinai Governorate, Egypt. The aim of this investigation to study the effect of two sowing dates (15 th October., and 15 th November), two irrigation treatments (100% for water requirements for pea , which is 2100 m 3 distributed through the growth stage to irrigation every day and irrigated every two days by half of these require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Tiwari et al (24) also observed a significant influence of interaction between sowing dates and varieties on plant height, number of primary branches. Abuo El-kasem and Elkassas (1) showed that sowing (15 th October) gave the highest values of all growth parameters; i.e., plant height, number of branches, number of leaves as well as pod number plant -1 and yield plant -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Tiwari et al (24) also observed a significant influence of interaction between sowing dates and varieties on plant height, number of primary branches. Abuo El-kasem and Elkassas (1) showed that sowing (15 th October) gave the highest values of all growth parameters; i.e., plant height, number of branches, number of leaves as well as pod number plant -1 and yield plant -1 .…”
Section: Introductionmentioning
confidence: 99%